The VEGFR2, COX‐2 and MMP‐2 polymorphisms are associated with clinical outcome of patients with inoperable non‐small cell lung cancer. Issue 10 (3rd June 2015) - Butkiewicz, Dorota; Krześniak, Małgorzata; Drosik, Anna; Giglok, Monika; Gdowicz‐Kłosok, Agnieszka; Kosarewicz, Agata; Rusin, Marek; Masłyk, Barbara; Gawkowska‐Suwińska, Marzena; Suwiński, Rafał
<x xml:space="preserve">Abstract</x> Certain common inherited variations in genes involved in tumor angiogenesis, progression and metastasis may contribute to cancer therapy outcome and prognosis by altering the gene expression and protein activity. In this report, we examined the effect of functional polymorphisms in MMP‐1, MMP‐2, MMP‐3, VEGF, VEGFR2, FGFR4 and COX‐2 genes on overall (OS) and progression‐free survival (PFS) of 350 Caucasian patients with inoperable non‐small cell lung cancer (NSCLC). The results of multivariate analysis indicated that VEGFR2 ‐906C and COX‐2 ‐1195G alleles were strongly associated with poor OS and PFS (p = 0.002 and 0.015, respectively, for OS; p = 0.009 and 0.015, respectively, for PFS), while MMP‐2 ‐1306 T allele carriers had significantly reduced PFS (p = 0.010). Moreover, an increased risk of death and progression was significantly associated with the number of adverse alleles for VEGFR2/COX‐2 (p = 0.0005 for OS and 0.0006 for PFS in >1 adverse allele carriers) and VEGFR2/COX‐2/MMP‐2 combinations (p = 0.0003 for OS and 0.0001 for PFS in patients with >2 adverse alleles). Finally, VEGFR2 TC/CC, COX‐2 AG/GG and MMP‐2 CT/TT genotypes as well as "at risk" allele combinations were identified as independent predictors of unfavorable OS and PFS in the group. In conclusion, the data suggest that selected VEGFR2, COX‐2 and MMP‐2 polymorphisms may be potential prognostic markers in unresectable NSCLC treated with radiotherapy with or without chemotherapy, although further validation studies are warranted to confirm our observations.